Assumptions to the model of managing knowledge workers in modern organizations = Założenie do modelu zarządzania pracownikami wiedzy we współczesnych organizacjach - Igielski, Michał (Zielona Góra: Faculty of Economics and Management Press)
Changes in the twenty-first century are faster, suddenly appear, not always desirable for the smooth functioning of the company. This is the domain of globalization, in which new events - opportunities or threats, forcing the company all the time to act. More and more things depend on the intangible assets of the undertaking, its strategic potential. Certain types of work require more knowledge, experience and independent thinking, and custom than others.
Keywords: model zarządzania; przedsiębiorstwo; uwarunkowania rynkowe; wiedza; pracownik wiedzy; management model; modern organizations; market conditions; knowledge; knowledge worker